An Infrequent Case of Renal Secondary Hyperparathyroidism in a Juvenile Dog - Ramasmy, Ravi; Venkatesakumar, Elumalai; Senthilkumar, Gurunathan; Balasubramaniam, Gurusamypalayam Arumugam; Sathyabama , Thangavelu; Sumathi, Devaraj (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Renal secondary hyperparathyroidism and renal osteodystrophy are the most common sequela of chronic kidney disease in young dogs. Clinically important renal secondary hyperparathyroidism is rarely reported in dogs. An eight month old male Labrador retriever dog was presented with history of facial swelling, anorexia, general weakness, weight loss, nasal discharge, nausea difficulty in breathing and prolonged urination for past three months. The animal showed marked, symmetric non-painful swelling of the maxilla with dental displacement and mild bilateral serous nasal discharge. Haematology revealed anaemia and neutrophilic leukocytosis. Serum biochemistry showed increase in blood urea nitrogen, creatinine, phosphorus, parathyroid hormone (PTH) and decrease in ionized calcium. Lateral radiograph of maxilla revealed decrease in bone radiopacity. Ultrasonography of kidneys revealed small sized kidney, indistinct corticomedullary junction, hyperechoic foci in the renal parenchyma and severe loss of cortex with hyperechoic capsule. Computed Tomography of the head showed poor mineralization of the facial and calvarial bones, especially the maxillary and frontal bone. Histopathology revealed proliferation of fibrous tissue in interstitium leads to compression of glomeruli and loss of glomerular tuft, mineralization of necrotic tubules and peritubular fibrosis. Renal secondary hyperparathyroidism should be considered one of the differential diagnosis in young dogs with bilateral facial swelling.
Keywords: Hyperparathyroidism; An Infrequent; Juvenile Dog